Parceria dos empréstimos entre as bibliotecas universitárias da cidade de Frederico Westphalen - Silva, Ricardo Cesar (2016)
The need for greater administrative efficiency in the public sector makes the society reveal their need for quality in products and services. One way to meet the users/customers expectations is through partnerships. This thesis proposes to establish a partnership model between Universities from the city of Frederico Westphalen for interlibrary loans of bibliographic material available in local institutions. The relevance is mainly promotes growing access to information and knowledge between stakeholders from these institutions (academic community and institutions). To this purpose, a case study methodology was used, with a qualitative approach and a descriptive and exploratory character. The steps to carry out this research were (i) data collection with partner institutions (semi-structured questionnaire) and (ii) research and collect data from institutions that offer interlibrary loans. Data was organized according to Process Management - Unified Modeling Language (UML) - and presentation of data with Use Case and Activity diagrams, laid out in a Procedures Manual. The preparation of this manual, a practical and direct result of this thesis, aims to standardize and streamline how the relationship between partner libraries should be and the procedures for the use of this service by the user/client. Besides, it offers a set of performance indicators, in order to measure if the service is meeting the expectations of users/clients and institutions involved. In general lines, the work proved to be feasible with the possibility of making available over 200 thousand works, economic savings in the replication of institutional collections and a model of loans, between libraries, that can be used in other cities.